Clinical Trial Design and Endpoints for Stage IV Melanoma in the Modern Era. Issue 1 (January 2017) - Izar, Benjamin; Regan, Meredith M.; McDermott, David F.
Abstract : Abstract: Immunotherapies and targeted therapies for the treatment of metastatic or advanced melanoma produce unique patterns of antitumor response. Conventional outcome measures, such as median progression-free and overall survival, may not be ideally suited to identify all patients who derive a benefit from such therapies. Therefore, the introduction of additional endpoint measures, such as milestone comparisons, may be necessary to characterize the potential benefit of such treatment approaches. Immune checkpoint inhibitors induce durable responses in a portion of patients that may continue after treatment cessation. Measuring the associated treatment-free interval, treatment-free survival, and associated patient-reported outcomes could provide important information when implemented in prospective clinical trials. In this article, we discuss the limitations of current endpoint measures and the potential advantage of using novel endpoints and how these might be used in designing clinical trials to address critical unanswered questions for patients with metastatic melanoma.